Micro Intervention Model of Social Work Values in Handling Radicalized Children - Nufus, Belgis Hayyinatun; Nulhaqim , Soni Akhmad; Rusyidi, Binahayati; Napsiyah, Siti; Trihartono, Agus; Santoso, Budhy (UIN Sunan Gunung Djati, 2026)
This study examines the contribution of micro-level social work practices to the rehabilitation of children exposed to radicalism in Indonesia. The study aims to explain how seven core individual-focused social work values individualization, purposeful expression of feelings, controlled emotional involvement, acceptance, a non-judgmental attitude, self-determination, and confidentiality, are operationalized in casework-based counter-radicalization interventions. Rather than positioning child rehabilitation solely as a security agenda, this study conceptualizes it as a process of restoring life capabilities oriented toward the best interests of the child. The research adopts a qualitative case study design, with data collected between 2019 and 2023 through observation, in-depth interviews, and document analysis. The study purposively selected informants from cross-sectoral professionals directly involved in the rehabilitation of children exposed to radicalism. The researchers conducted data analysis through systematic processes of coding, categorization, and thematic interpretation to ensure contextual depth and the credibility of findings. The findings demonstrate that the seven social work values consistently operate in forming a recurrent intervention pattern, moving from values to stages of intervention and ultimately shaping the meaning of rehabilitation outcomes. These values guide holistic assessment, inform the selection of intervention techniques, and frame rehabilitation success not in terms of ideological compliance or zero risk, but as the restoration of emotional regulation, the recovery of child agency, and the reopening of future life orientations. Rehabilitation practices unfold through interprofessional collaboration among social workers, psychologists, educators, religious leaders, and security officers, with social workers playing a pivotal role as ethical gatekeepers in navigating tensions between child welfare logic and state security logic. The most critical challenge emerges during social reintegration, when institutional rehabilitation outcomes often fail to align with community acceptance, underscoring the need to expand interventions beyond the micro level toward community-based approaches. This study contributes theoretically by extending social work value theory into the context of child deradicalization, a field largely dominated by security-oriented approaches. It also offers a practical contribution by proposing a value-based micro-intervention framework for the rehabilitation of children exposed to radicalism in Indonesia.